PENGARUH LEVERAGE, UKURAN PERUSAHAAN, KOMITE AUDIT DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAXAVOIDANCE DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Lisa Octaviana, 15.05.52.0134; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the effect of leverage, firm size, audit committee and institutional ownership on tax avoidance with profitability as a moderating variable. This research was conducted in Indonesia by using an analysis unit of manufacturing companies that have gone public.The population of this research is manufacturing companies listed on the Indonesia Stock Exchange. The sample included in the criteria of this study were 193 companies for 3 years and selected as a sample of 148 companies with a sampling method using purposive sampling.The data in this study were analyzed by multiple linear regression analysis techniques. The results of this study indicate that the leverage variable has a significant positive effect on tax avoidance, firm size variables have a positive and insignificant effect on tax avoidance, audit committee variables and institutional ownership have no significant negative effect on tax avoidance, profitability variables are able to moderate the influence of leverage on tax avoidance and profitability not able to moderate the influence of company size on tax avoidance.